Determinants of housing satisfaction in Klang Valley, Malaysia - Tan, Teck-Hong * (School of Business, Sunway University, 2011)
Housing policies and programs have long been developed and implemented to ensure that all have access to adequate housing in Malaysia. Despite efforts by both public and private housing providers, there are various issues relating to the housing delivery system that have undermined the success of housing achievement for the past 30 years. In order to achieve sustainability in the housing industry, public and private housing providers should regulate their housing activities to suit homeowners? needs and wants by examining factors which account for housing satisfaction or dissatisfaction among homeowners. Determinants found significant in the study were housing, neighborhood, location and socio-demographic variables. In addition, the degree of housing satisfaction may depend on the types of externalities of homeownership that homeowners are expected to receive.